Impact of Dietary Betaine and Metabolizable Energy Levels on Profiles of Proteins and Lipids, Bioenergetics, Peroxidation and Quality of Meat in Japanese Quail - Sabry M. El-Bahr; Saad Shousha; Wasseem Khattab; Ahmed Shehab; Osama El-Garhy; Hoda El-Garhy; Shereen Mohamed; Omar Ahmed-Farid; Ahmed Hamad; Islam Sabike (Animals, 2021)
Three different diets were formulated with three levels of metabolizable energy (ME) (optimum; 2900, restricted; 2800 and low; 2700 kcal ME/kg diet) without or with (0 and 0.15%) betaine supplementation in 2 × 3 factorial design to evaluate the effect of six experimental diets on performance, proteins and lipids profiles, bioenergetics, peroxidation and meat quality of Japanese quail. Therefore, 360 quails allocated into six groups in a 23-day experiment. Dietary betaine and ME levels did not affect the performance, meat energy indices (ATP and AMP) and malondialdehyde (MDA) levels of Japanese quail meat. Dietary betaine and/or ME levels induced significant changes in serum triacylglycerol (TAG), total cholesterols (TC), low-density lipoprotein cholesterol (LDL-c), very low-density lipoprotein cholesterol (VLDL-c), meat total lipids and cholesterol of Japanese quail. Optimum and restricted ME levels reduced total volatile basic nitrogen (TVBN) whereas dietary betaine increased ecosapentaenoic (EPA), docosahexaenoic acids (DHA) and glutamine concentrations in breast meat of Japanese quail. Dietary betaine and low energy diet improved cooking loss, thawing loss (ThL) and water holding capacity (WHC) in breast meat of Japanese quail. Conclusively, dietary betaine improved meat quality of Japanese quail fed diets containing either restricted or low ME by enrichments the meat with omega-3 fatty acids and reduction of lipids levels.